REFORMASI POLITIK, DEMOKRASI INDONESIA: ANTARA REALITA, CITA-CITA DAN UTOPIA - Nurjaman, Asep (Jurnal Bestari, 2001)
As a nation state, indonesia has three model of democration, namely liberal democration, ?Democrary Terpimpin ? and ? Democrary pancasila? . liberal democration has a good initiation on democratization, an grow-up until the success story of the General Election on 1955. After that, the democration become complicated ad arena of conflic of interest. Both of ? Democrary Terpimpin? and ? Democrary Pancasila? . in the prsent time, democration and democratization in indonesia har to develop because the people do not has social deisciplines, as a one of the basic principle of democration practices.